The Presence of the DNA Repair Genes mutM, mutY, mutL, and mutS is Related to Proteome Size in Bacterial Genomes - Garcia-Gonzalez, Aurian; Rivera-Rivera, Ruben; Massey, Steven E. (Frontiers in Genetics, 2012)
DNA repair is expected to be a major modulator of underlying mutation rates, however the factors affecting the distribution and complexity of DNA repair pathways have not been determined. The Proteomic Constraint hypothesis proposes that mutation rates have evolved to be inversely proportional to the amount of heredity information contained in a genome, effectively the proteome. Thus, organisms with larger proteomes are expected to possess more efficient DNA repair. It is shown that an important factor influencing the presence or absence of the four DNA repair genes mutM, mutY, mutL and mutS is the size of the bacterial proteome, consistent with this hypothesis. This is true of intracellular and free-living bacteria. In addition, the relationship of DNA repair to genome GC content was examined. In principle, the presence of a DNA repair pathway biased in the types of mutations it corrects has the potential to alter the underlying GC content. The products of the base excision repair genes mutM and mutY both correct GC->AT mutations and the presence of these genes were both positively correlated with genome GC content, consistent with their repair mechanism. In contrast, the presence of the mismatch repair genes mutS and mutL are not correlated with genome GC content, consistent with their involvement in an unbiased DNA repair pathway. However, when phylogenetic analysis is conducted, the relationship between presence of mutM and mutY genes and GC bias becomes less clear, indicating a more complex relationship between DNA repair and GC content.